Growth and convergence in the Caribbean - Carter, Adrian (2000)
Assesses the degree of economic convergence of CARICOM member countries utilizing a stochastic Solow growth model. Investigates the speed of convergence in per capita output of the individual economies to their country-specific steady growth rate and attempts to draw implications therefrom. Reveals that a union between OECS and Barbados may be sustainable.